2012
DOI: 10.3390/ijms131216119
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of CD4+ T Cell Adhesion to Cerebral Microvascular Endothelium by the β-Chemokines CCL2 and CCL3

Abstract: In Multiple sclerosis (MS), circulating lymphocytes cross the blood–brain barrier (BBB) and accumulate at sites of antigenic challenge. This process depends on specific interactions between lymphocytes and cerebral microvascular endothelium that involve endothelial activation by cytokines and the presence of chemokines. Chemokines play a key role in the orchestration of immune responses, acting both as chemoattractants and activators of leukocyte subsets. In the present study, we investigated the effects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 54 publications
(59 reference statements)
1
10
0
Order By: Relevance
“…However, monocyte attachment was increased twofold in WNV-MAD78-infected cultures, which is consistent with the observation that this virus induced higher levels of CCL5 expression in HBMECs compared with WNV-NY. As expected, high levels of THP-1 cells bound to control cells treated with TNF-α ( Liu & Dorovini-Zis, 2012 ). Together, these findings suggest that the chemokine response in HBMEC monolayers to non-pathogenic strains of WNV may be more efficient at attracting leukocytes compared with highly pathogenic strains of WNV.…”
supporting
confidence: 74%
“…However, monocyte attachment was increased twofold in WNV-MAD78-infected cultures, which is consistent with the observation that this virus induced higher levels of CCL5 expression in HBMECs compared with WNV-NY. As expected, high levels of THP-1 cells bound to control cells treated with TNF-α ( Liu & Dorovini-Zis, 2012 ). Together, these findings suggest that the chemokine response in HBMEC monolayers to non-pathogenic strains of WNV may be more efficient at attracting leukocytes compared with highly pathogenic strains of WNV.…”
supporting
confidence: 74%
“…Interestingly, it was also detected in plasma samples from ZIKV + patients (our results and those in reference 39 ). Moreover, CCL5 and CCL2 are known mediators of leukocyte recruitment to the BBB ( 57 , 58 ), thus suggesting that the local environment in ZIKV-infected BBB could favor immune cell recruitment/migration and access to the CNS. Besides the upregulation of chemoattractants, one of the key observations of this study was the marked increase in CAM expression, namely, ICAM-1, VCAM-1, and E-selectin, in ZIKV-infected hBLECs.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the expression of specific cell adhesion molecules was induced exclusively in Cup/EAE mice, suggesting that these treatments have produced an environment conducive to inflammatory cell activity. Moreover, we identified upregulation of Ccl2 , Ccl3 , and Cxcl10 , which encode chemokines that act as chemoattractants for various inflammatory cells, including T lymphocytes (Carr, Roth, Luther, Rose, & Springer, ; K. K. Liu & Dorovini‐Zis, ; Millward, Caruso, Campbell, Gauldie, & Owens, ), dendritic cells (Xu, Warren, Rose, Gong, & Wang, ), monocytes (Moreno et al, ; Price et al, ), and microglia (Clarner et al, ; Moreno et al, ). Interestingly, the cerebella of mice showed relatively weaker induction of these chemokines, despite that obvious involvement of this region in EAE by our work and those of others.…”
Section: Discussionmentioning
confidence: 99%